Vision, Harvard students look ahead a multidisciplinary approach - Devash, Isaac (Harvard Business School Press, 1994)
In this work, Harvard undergraduate and graduate students write, from the point-of-view of their various disciplines, about what they believe our world will look like in the future. Expressing issues of concern to young people everywhere, this book challenges us to think seriously about the future.